Comparison of the effectiveness of emotional expression through writing and narration in reducing post-traumatic stress and postpartum depression among women undergoing emergency cesarean section - Ali Navidian; Somayyeh Khazaeian (Tehran University of Medical Sciences, 2023)
Background & Aim: The utilization of emotional expression methods, including narrative counseling and written emotional expression, has been shown to be efficacious in mitigating the intensity of diverse psychological issues such as depression and acute stress, particularly following traumatic events. Additionally, emergency cesarean section is commonly acknowledged as a traumatic event that may lead to psychological challenges for the mother. The purpose of this research was to compare the effectiveness of emotional expression through writing and narration in reducing post-traumatic stress and postpartum depression among women undergoing emergency cesarean section. Methods & Materials: This quasi-experimental study was conducted in Zahedan, involving a total of 120 women who underwent emergency cesarean section and were admitted to Ali Ibn Abi Talib (AS) hospital during the period of 2021-2022. The participants were selected using convenience sampling and were randomly divided into three groups: written emotional expression, narration and control, with each group consisting of 40 participants. The intervention consisted of one face-to-face session and two non-face-to-face sessions. Data collection involved the use of the Edinburgh Depression Questionnaire and PTSD assessments, administered before and six weeks after the intervention across all three groups. The data were analyzed using SPSS version 24, employing descriptive and inferential tests such as ANOVA and Tukey's post hoc analysis. Results: The results showed a significant decrease in the average scores of post-traumatic stress and postpartum depression in the written emotional expression and narration groups, compared to the control group, after the intervention (P<0.05). However, before the intervention, there were no significant differences observed among the three groups (P>0.05). Furthermore, a higher mean difference was observed in both post-traumatic stress and postpartum depression scores before and after the intervention in the written emotional expression group, compared to the narration group, indicating a greater effect of written emotional expression (P<0.001). Conclusion: Based on the research findings, highlighting the positive effect of both narration and written emotional expression, it is recommended to incorporate these techniques as supplementary components within comprehensive educational and care programs for women experiencing traumatic childbirth.